Development of a Coupled and Self-adaptive Robot Hand with Linear Empty-trip Transmission - Song Jiuya; Dang Linan; Qi Jingchen; Wei Yuangen; Zhang Wenzeng (Jixie chuandong)
The traditional coupled and self-adaptive fingers realize firstly coupling and secondly self-adaptive hybrid grasping mode with three springs and two sets of independently transmission mechanisms,which have disadvantages of complexity in mechanisms,huge consuming in power,and difficulty in spring selection.Aiming at the problem,a novel coupled and self-adaptive underactuated finger mechanism,called COSA-LET finger is designed. The COSA-LET finer includes multiple racks,two toggle blocks,two limiting blocks,and two springs,which has two joints driven by one motor and a serial transmission mechanism. The coupling function of COSA-LET finger is realized by two opposite-direction racks,and a gear with a spring and a limiting block,the de-coupling problem of the finger in the self-adaptive stage is solved by dividing torque of the motor into two joint shafts with a spring and the delay-ticking transmission effect of two toggle blocks in linear empty-trip racks. Grasping force analysis and experimental results show that the COSA-LET robotic hand with three COSA-LET fingers has the coupled and self-adaptive hybrid grasping function,enable to adapt objects of different shapes and sizes,autonomously switch between the coupled mode and the self-adaptive mode.